A new record of Larnaca Walker, 1869 (Orthoptera: Gryllacrididae: Gryllacridinae) from China with description of a new species - Bian, Xun; Guo, Li-Ying; Shi, Fu-Ming (Zootaxa, 2015)
In the paper, Larnaca is recorded from the Chinese fauna for the first time. A single new species, Larnaca (Larnaca) emarginata Bian, Guo & Shi, sp. nov., is described. This extends the distribution of the genus Larnaca from Lao Cai prov., Vietnam to Yunnan prov. in southwestern China.